Kontribusi Sektor Pariwisata Terhadap PDRB di Kabupaten Raja Ampat - Elprida Sigiro, Ely; Fabiyan Pudyo , Audi (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
The leading sector is essential for regional economic growth. This study aims to determine how the tourism sector contributes to the GRDP of Raja Ampat Regency and whether the tourism sector in Raja Ampat Regency is a leading sector. The data used in this study are GRDP data from the business field in Raja Ampat Regency in 2014-2018. The method used in this research is Location Quotient (LQ). The results of the LQ analysis show that the tourism sector in Raja Ampat Regency is not a leading sector. In improving the tourism sector, the leading sector is dynamic, so it can change every year. Changes from non-leading to leading sectors can be stimulated by the development of supporting infrastructure in the form of increased human resources and accessibility to these tourist areas.